Combining Deep Eutectic Solvents with TEMPO‐based Polymer Electrodes: Influence of Molar Ratio on Electrode Performance. Issue 2 (7th December 2022) - Uhl, Matthias; Geng, Tanja; Schuster, Philipp A.; Schick, Benjamin W.; Kruck, Matthias; Fuoss, Alexander; Kuehne, Alexander J. C.; Jacob, Timo
Abstract: For sustainable energy storage, all‐organic batteries based on redox‐active polymers promise to become an alternative to lithium ion batteries. Yet, polymers contribute to the goal of an all‐organic cell as electrodes or as solid electrolytes. Here, we replace the electrolyte with a deep eutectic solvent (DES) composed of sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) and N ‐methylacetamide (NMA), while using poly(2, 2, 6, 6‐tetramethylpiperidin‐1‐yl‐oxyl methacrylate) (PTMA) as cathode. The successful combination of a DES with a polymer electrode is reported here for the first time. The electrochemical stability of PTMA electrodes in the DES at the eutectic molar ratio of 1 : 6 is comparable to conventional battery electrolytes. More viscous electrolytes with higher salt concentration can hinder cycling at high rates. Lower salt concentration leads to decreasing capacities and faster decomposition. The eutectic mixture of 1 : 6 is best suited uniting high stability and moderate viscosity. Abstract : Sustainable battery technology: The combination of deep eutectic solvents (DESs) with TEMPO‐based electrodes opens a new way to environmentally friendly energy storage in all‐organic batteries. Especially the eutectic mixture of the DES composed of sodium bis(trifluoromethanesulfonyl)imide and N ‐methylacetamide enables stable and efficient cycling of the polymer electrodes.